Space, Personhood and Movement in Amerindian Sociality: on Huni Kuin Modes of Sociality - McCallum, Cecilia (Revista de Antropologia, 2015)
The article explores Huni Kuin practices that simultaneously constitute sociality, persons and their relationship with the environment. When creating themselves in a material and social sense in inter-subjective processes occurring in specific space-time configurations, they forge contingent connections of ownership between people and places, and create the conditions to open temporary clearings of human space in a world guarded and cared for by non-human entities. The article begins by recalling the commitment of Huni Kuin leaders to defending their ownership rights and insisting on the demarcation of indigenous lands, as specified by Brazilian law, for which they use a non-indigenous discursive language. The main focus of this essay, however, is on indigenous practices of everyday life. It explores the notion that, in an important sense, for this Amazonian people, territory is not fixed, but depends on the constant transformation of the co-presence of Huni Kuin who are involved in relationships with each other and with other entities and persons from the surrounding world.